2015
DOI: 10.1073/pnas.1416196112
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic glutamate receptor 3 activation is required for long-term depression in medial prefrontal cortex and fear extinction

Abstract: Clinical studies have revealed that genetic variations in metabotropic glutamate receptor 3 (mGlu 3 ) affect performance on cognitive tasks dependent upon the prefrontal cortex (PFC) and may be linked to psychiatric conditions such as schizophrenia, bipolar disorder, and addiction. We have performed a series of studies aimed at understanding how mGlu 3 influences PFC function and cognitive behaviors. In the present study, we found that activation of mGlu 3 can induce long-term depression in the mouse medial PF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
86
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(97 citation statements)
references
References 46 publications
11
86
0
Order By: Relevance
“…Similarly, 100 μM CCh also failed to induce any form of mLTD in these PCP-treated mice (n = 5; 97.1 ± 6.3%). In contrast, a previously reported form of mGlu 2/3 agonist LY379268-mediated glutamatergic LTD (Walker et al, 2015) was unaffected in the PCP-treated mice (Supplementary Figure S5a and b). This indicated that the deficit in mLTD is specific to deficits in muscarinic plasticity.…”
Section: Repeated Pcp Treatment Induces a Deficit In Mltd That Can Bementioning
confidence: 56%
See 1 more Smart Citation
“…Similarly, 100 μM CCh also failed to induce any form of mLTD in these PCP-treated mice (n = 5; 97.1 ± 6.3%). In contrast, a previously reported form of mGlu 2/3 agonist LY379268-mediated glutamatergic LTD (Walker et al, 2015) was unaffected in the PCP-treated mice (Supplementary Figure S5a and b). This indicated that the deficit in mLTD is specific to deficits in muscarinic plasticity.…”
Section: Repeated Pcp Treatment Induces a Deficit In Mltd That Can Bementioning
confidence: 56%
“…One can also argue that this mLTD deficit is a general dysfunction in overall plasticity-related mechanisms in the PFC. However, we found that glutamatergic LTD mediated by the group II mGlu receptor mGlu3 (Walker et al, 2015) is intact in the PFC after PCP treatment, indicating PFC synapses can still undergo plastic changes in these mice. It is possible that mLTD and group II mGlu receptor-mediated LTD can reflect plasticity in distinct synapses in the PFC, thus serving distinct functions, and repeated PCP treatment leads to selective mLTD deficits and deficits in functions only related to this form of muscarinic plasticity.…”
Section: Role Of M 1 Pam In Pcp-treated Micementioning
confidence: 72%
“…Recent evidence suggests that LTD in the mPFC is mediated through postsynaptic mGluR3 but not mGluR2. An mGluR3 negative allosteric modulator blocked LTD induced by LY379268 but not acute synaptic inhibition by LY379268 [43]. We did not measure LTD but our data on acute inhibitory effects of LY379268 would be consistent with the involvement of mGluR2 rather than mGluR3.…”
Section: Discussionmentioning
confidence: 84%
“…Group II mGluR antagonists had beneficial effects in an Alzheimer's Disease mouse model, improving cognitive functions and anxiety [22]. However, mGluR3 negative allosteric modulators impaired extinction of conditioned fear [43]. These findings suggest that group II mGluRs play complex roles in cognitive-affective functions and disorders and could also be useful targets to normalize deficits associated with pain such as medial prefrontal cortical dysfunction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation